NATIONAL SPECIFICS OF GESTURES AND HABITS IN ENGLISH AND UZBEK CULTURES - Kamolova Rushana Ibodovna; Yusupova Shoira Botirovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores the national specifics of gestures and habits in English and Uzbek cultures. It analyzes how non-verbal communication and everyday behaviors reflect deeper cultural values such as individualism, collectivism, hospitality, and politeness. By comparing the similarities and differences between these two cultures, the article emphasizes the importance of cultural awareness in promoting effective intercultural communication. The study concludes that understanding gestures and habits can bridge cultural gaps and enhance social interaction in a globalized world.